Docosahexaenoic Acid Alleviates Palmitic Acid-Induced Inflammation of Macrophages via TLR22-MAPK-PPARγ/Nrf2 Pathway in Large Yellow Croaker (Larimichthys crocea) - Dan Xu; Kun Cui; Qingfei Li; Si Zhu; Junzhi Zhang; Shengnan Gao; Tingting Hao; Kangsen Mai; Qinghui Ai (Antioxidants, 2022)
Palmitic acid (PA) is a saturated fatty acid (SFA) that can cause an inflammatory response, while docosahexaenoic acid (DHA) is always used as a nutritional modulator due to its anti-inflammatory properties. However, the potential molecular mechanism is still not completely elucidated in fish. Herein, the PA treatment induced an inflammatory response in macrophages of large yellow croaker (Larimichthys crocea). Meanwhile, the mRNA expression of Toll-like receptor (TLR)-related genes, especially tlr22, and the phosphorylation of the mitogen-activated protein kinase (MAPK) pathway were significantly upregulated by PA. Further investigation found that the PA-induced inflammatory response was suppressed by tlr22 knockdown and MAPK inhibitors. Moreover, the results of the peroxisome proliferator-activated receptor γ (PPARγ) agonist and inhibitor treatment proved that PPARγ was involved in the PA-induced inflammation. PA treatment decreased the protein expression of PPARγ, while tlr22 knockdown and MAPK inhibitors recovered the decreased expression. Besides, the PA-induced activation of Nrf2 was regulated by p38 MAPK. Furthermore, DHA-executed anti-inflammatory effects by regulating the phosphorylation of the MAPK pathway and expressions of PPARγ and Nrf2. Overall, the present study revealed that DHA alleviated PA-induced inflammation in macrophages via the TLR22-MAPK-PPARγ/Nrf2 pathway. These results could advance the understanding of the molecular mechanism of the SFA-induced inflammatory response and provide nutritional mitigative strategies.